2003
DOI: 10.1046/j.1471-4159.2003.01508.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NADH oxidation by chloramphenicol in the freely moving rat measured by picosecond time‐resolved emission spectroscopy

Abstract: Owing to the lack of methods capable to monitor the energetic processes taking place within small brain regions (i.e. nucleus raphe dorsalis, nRD), the neurotoxicity of various categories of substances, including antibiotics and psycho-active drugs, still remains difficult to evaluate. Using an in vivo picosecond optical spectroscopy imaging method, we report that chloramphenicol (CAP), besides its well-known ability to inhibit the mitochondria protein synthesis, also influences the NADH/ NAD + redox processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 55 publications
2
27
0
1
Order By: Relevance
“…However, these current data also suggest that the remaining non-neurotoxicant chloramphenicol was capable of inducing cytoskeleton toxicity in the NT2.N/A model, including degeneration of NFs and more significantly GFAP at sub-cytotoxic concentrations and a relative 15% decrease in the number of astrocytes at concentrations cytotoxic to 50% of the cell population. Chloramphenicol is a broad spectrum antibiotic, associated occasionally with dose unrelated myelotoxicity (Kong et al 2000) and adverse CNS effects such as confusion, headache and convulsions, linked with inhibition of mitochondrial complex I and subsequent impaired ATP production (Mottin et al 2003). During in vitro studies using rat cortical neurons, Schmuck et al (2000) noted that cytoskeletal effects induced by a variety of unrelated neurotoxic chemicals seemed to be subsequent to ATP depletion and they concluded that cytoskeletal damage is an endpoint mechanistically related to numerous degenerative neurotoxic effects at sub-cytotoxic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…However, these current data also suggest that the remaining non-neurotoxicant chloramphenicol was capable of inducing cytoskeleton toxicity in the NT2.N/A model, including degeneration of NFs and more significantly GFAP at sub-cytotoxic concentrations and a relative 15% decrease in the number of astrocytes at concentrations cytotoxic to 50% of the cell population. Chloramphenicol is a broad spectrum antibiotic, associated occasionally with dose unrelated myelotoxicity (Kong et al 2000) and adverse CNS effects such as confusion, headache and convulsions, linked with inhibition of mitochondrial complex I and subsequent impaired ATP production (Mottin et al 2003). During in vitro studies using rat cortical neurons, Schmuck et al (2000) noted that cytoskeletal effects induced by a variety of unrelated neurotoxic chemicals seemed to be subsequent to ATP depletion and they concluded that cytoskeletal damage is an endpoint mechanistically related to numerous degenerative neurotoxic effects at sub-cytotoxic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Although other techniques using small optical fibers exist (Kudo et al, 1992;Nakamura et al, 1999;Duff Davis and Schmidt, 2000;Mottin et al, 2003), our technique, just like the one used by others (Bradley et al, 2008;LeChasseur et al, 2008;Zhang et al, 2009) has the advantage of combining electrical and optical readings. In our case, two electrical sensors have joined the optical fiber.…”
Section: The Micro-optrodementioning
confidence: 97%
“…They were used to record from intact heart (Bowmaster et al, 1991;Krauthamer et al, 1991;Neunlist et al, 1992) and neuronal (Kudo et al, 1989(Kudo et al, , 1992; Duff Davis and Schmidt, 2000;Mottin et al, 2003) cells. However, these sensors are relatively large (diameter > 125 m), thus comparable to microendoscopes.…”
Section: Introductionmentioning
confidence: 99%
“…Although these cannot transmit images, they are inexpensive and can be used to record changes in fluorescence independent of the depth of the structure. These 'optrodes' or 'optodes' have been used in conjunction with voltage and calcium-sensitive dyes to monitor cellular fluorescence changes in the intact heart (Bowmaster et al, 1991;Lee et al, 1984;Neunlist et al, 1992), nervous system (Kudo et al, 1989(Kudo et al, , 1992Nakamura et al, 1999), and in the brains of freely moving animals (Duff Davis and Schmidt, 2000;Mottin et al, 2003). In the main, these studies used relatively large optical fibers (100's of microns diameter) to record gross changes in activity from large volumes of tissue.…”
Section: Introductionmentioning
confidence: 99%